2007
DOI: 10.1063/1.2713784
|View full text |Cite
|
Sign up to set email alerts
|

High quality Fe3−δO4∕InAs hybrid structure for electrical spin injection

Abstract: Single crystalline Fe 3−␦ O 4 ͑0 ഛ ␦ ഛ 0.33͒ films have been epitaxially grown on InAs ͑001͒ substrates by molecular beam epitaxy using O 2 as source of active oxygen. Under optimum growth conditions, in situ real time reflection high-energy electron diffraction patterns, along with ex situ atomic force microscopy, indicate that ͑001͒ Fe 3−␦ O 4 can be grown under step-flow-growth mode with a characteristic ͑ ͱ 2 ϫ ͱ 2͒R45 surface reconstruction. X-ray photoelectron spectroscopy demonstrates the possibility of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Recent interest has been directed at the use of semiconducting substrates. [10][11][12][13][14][15] However, there are only sparse experimental reports 10,13 on interface chemistry and interface reactions, although based on thermodynamic considerations such interfaces might not be stable. 16 In this work, we examine this problem and investigate the chemical nature of Fe 3 O 4 films grown on GaAs͑100͒ substrates and their respective interfaces.…”
mentioning
confidence: 99%
“…Recent interest has been directed at the use of semiconducting substrates. [10][11][12][13][14][15] However, there are only sparse experimental reports 10,13 on interface chemistry and interface reactions, although based on thermodynamic considerations such interfaces might not be stable. 16 In this work, we examine this problem and investigate the chemical nature of Fe 3 O 4 films grown on GaAs͑100͒ substrates and their respective interfaces.…”
mentioning
confidence: 99%
“…[21][22][23] It has been reported that asdeposited films have not only a Fe 3 O 4 phase but also the other phase such as an iron or an iron oxide according to their deposition conditions. 22,24,25) It has also been found that epitaxial Fe 3 O 4 films on the MgO show peculiar magnetic properties, 15,21) and that a polycrystalline Fe 3 O 4 film on the Si exhibits a large magnetoresistance of $ 7:4% at room temperature. 23) Additionally, epitaxial Fe 3 O 4 films have been prepared by post oxidation of an iron film.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, high oriented, epitaxial or polycrystalline Fe 3 O 4 films have been obtained by various deposition techniques such as NO 2 or O 2 assisted molecular beam epitaxy (MBE), 14,15) electron beam ablation, 16) pulsed laser deposition from -Fe 2 O 3 17,18) or Fe 3 O 4 19,20) as a target, and reactive sputtering from an iron target with the argon and oxygen mixture gas flow. [21][22][23] It has been reported that asdeposited films have not only a Fe 3 O 4 phase but also the other phase such as an iron or an iron oxide according to their deposition conditions.…”
Section: Introductionmentioning
confidence: 99%
“…8 Epitaxial thin films for post complementary metal-oxide-semiconductor digital integrated circuits 9 and high performance spin devices [10][11][12] require the surfaces to be atomically smooth with low defect densities in critical conditions. However the formation of 3D structures or islands on the III-V surfaces is found to be an important study to explore the growth mechanism.…”
mentioning
confidence: 99%
“…6,22 Oxide removal process of InAs substrate and the growth chamber are exactly same as reported in our previous publication. 12 With reference to the surface reconstruction diagram, 300-nm-thick InAs layer was grown under As-pressure with a beam-equivalent-pressure ratio of As to In of about 12. The As-pressure is almost between 5.8 ϫ 10 −6 to 6.2ϫ 10 −6 Torr throughout all the growth experiments.…”
mentioning
confidence: 99%